Characteristics of Kawa Daun with Differences in the Drying Time and Thickness of Arabica Coffee Leaves - Jeany Ristia; Anwar Kasim; Novelina Novelina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Kawa daun is a beverage that is typical of West Sumatra and is created from dried coffee leaves.The purpose of this study is to ascertain the water content of kawa daun powder, pH value, total dissolved solids, the hedonic test for steeping kawa daun during drying using a microwave, the thickness of the pile of Arabica coffee leaves, and the preferred brew of kawa daun tea among the panelists. This study used a completely randomized design (CRD) factorial pattern with 2 factors. Factor A drying time for 3, 7, and 11 minutes. Factor B number of piles of leaves 2, 4, 6, 8, and 10 leaves. The resulting coffee leaf powder and kawa daun brew were then tested using hedonic tests for color, aroma, and taste as well as water content, pH value, and total dissolved solids. The panelists' chosen and favorite kawa daun drink composition was dried with 10 piles of leaves for 11 minutes. The properties of coffee leaf powder include a water content of 4.11%, a pH value of 6.4, 1.3 °Brix of total dissolved solids, and hedonic scores of 4.95 (very like), 4.40 (like), and 4.80 (very like) for color, scent, and taste.